2011
DOI: 10.1088/0957-0233/22/8/085107
|View full text |Cite
|
Sign up to set email alerts
|

Efficient thermal error prediction in a machine tool using finite element analysis

Abstract: Thermally induced errors have a major significance on the positional accuracy of a machine tool. Heat generated during the machining process produces thermal gradients that flow through the machine structure causing linear and nonlinear thermal expansions and distortions of associated complex discrete structures, producing deformations that adversely affect structural stability. The heat passes through structural linkages and mechanical joints where interfacial parameters such as the roughness and form of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…However, it is often not clear how the relevant values should be set. It has been suggested that extensive preliminary experimentation is required with a FEA model in order to ensure good understanding and specification of parameters [13]. In practice, the possibility of undertaking extensive preliminary work may not exist.…”
Section: Thermal Compensationmentioning
confidence: 99%
“…However, it is often not clear how the relevant values should be set. It has been suggested that extensive preliminary experimentation is required with a FEA model in order to ensure good understanding and specification of parameters [13]. In practice, the possibility of undertaking extensive preliminary work may not exist.…”
Section: Thermal Compensationmentioning
confidence: 99%
“…Because of the inadequacy of in-situ sensing technology for thermal deformation measurement in the high-temperature state of the flame-cutting process, this section presents the FEA testing procedures [15] to obtain off-line data of thermal deformation and temperature-field variation under varied working conditions. Taking the 1/12 circumferential configuration of a straight-cutting task as the specified application example, a brief description of the setup steps of the FEA simulation in ANASY is as follows:…”
Section: Fea Testing Procedures For Thermal Deformation Elementsmentioning
confidence: 99%
“…Appling temperature and displacement boundary conditions. The model in Figure 3 under research has three major temperature constraints [15]: (a) contact resistance within the 151 combined surfaces is set to . The displacement boundary condition is that the interfaces of the workpiece are in completed constraint state.…”
Section: Fea Testing Procedures For Thermal Deformation Elementsmentioning
confidence: 99%
“…Parametric [16], FEA [17] and "black box" [18,19] approaches are often used to solve various problems. To obtain robust levels of accuracy in the models, significant effort can be required which in the case of black box models is in training, while for FEA it is in the determination of a variety of boundary conditions.…”
Section: Thermal Errorsmentioning
confidence: 99%